The Effectiveness of Using Kahoot! in Teaching Arabic Grammar in Terms of Interest and Learning Results/ فعالية استخدام كاهوت! في تعليم القواعد العربية من حيث الاهتمام ونتائج التعلم - Assesanti, Dheyana Yolanda (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2021)
Grammar is an important part of the Arabic language. Words can be arranged into a correct sentence when following the existing rules. Learning Arabic grammar in Indonesia has many difficulties that come from students and teachers such as students have a low interest in learning Arabic and teachers have not tried new methods,  techniques, and media in learning Arabic. So students' interest and motivation tend to be low towards learning Arabic. This research aims to find out the effectiveness of the use of Kahoot! games to improve the results and interests of learning Arabic students of class IX MTs N Balikpapan. This study uses quasi-experimental methods. Research samples are taken with random techniques. Data collection is done by means of tests,  questionnaires, observations, and interviews. The instrument validity test is conducted using the product-moment correlation formula. Reliability test using the Alfa Cronbach formula. Data analysis is done with prerequisite tests of analysis and hypothesis tests. The results showed that there was a significant difference in results and interests in learning Arabic between control classes and experimental classes. This is indicated by the significance value on the t-test of -4.867 < 0.05. The experimental class post-test average was higher than the control class post-test average (64.43 > 42.67).